The Effects of Self-Confidence and Vocabulary Mastery on Students’ Speaking Skill - suryadi suryadi (Journal of English Language Studies, 2018)
The purpose of this research are; 1) to determine the effects of self-confidence and vocabulary mastery on students’ speaking skill. 2) to know the effect of self-confidence on students’ speaking skill. 3) to know the effect of vocabulary mastery on students’s speaking skill. 4) to know the correlation between self-confidence and vocabulary mastery on students’ speaking skill. This research used is descriptive verification method with ex post facto and survey approach. The instruments used are questionnaires distributed to students. The results of this research are; 1) there is effects of self-confidence and vocabulary mastery on students’ speaking skill. 2) there is effect of self-confidence on students’ speaking skill.3) there is effect vocabulary mastery on students’ speaking skill. 4) there is a correlation between self-confidence and vocabulary mastery on students’ speaking skill.Keywords: self-confidence; speaking skill ; vocabulary mastery